(untitled) (Fiep Bulletin - online, 2011)
This is a historical study, which focuses about the history of Physical Education as discipline in public schools of Piaui, from 1939 to 1975, and the composition of its faculty members. The inclusion of Physical Education at school in Piaui was made through the creation of the Piaui Physical Education Inspection Department in April 3rd, 1939 by Act nº168, published in the Official State Daily nº 77 and included Physical Education into the Education Department. The initial delineation of the time limit of this study is justified by the insertion of Physical Education in Piaui school curricula in 1939 and its final delineation was defined by considering the first class of Physical Education teachers who were graduated from Federal University of Piaui in 1975. This study tries to contribute with others studies related to the history of Physical Education, analyzing how it was inserted, and also the teacher training of this area on Piaui Public Schools context. It was analyzed the reports, regulations, rules and teaching ordinances related to public education of that age. Besides these documents, we got oral sources by using semi-structured interviews: Three Physical Education teachers, who participated, contributed and experienced the period of construction of Physical Education in Piaui. Finally, it is essential to recognize that the universe of History is a reinvented history, focusing on present, and questioning the past. This work aimed to verify and respond our questions about how Physical Education was drawn in Piaui. We conclude that it was not different from the rest of Brazil, based on a standpoint of legality, but it differs on its legitimacy.